Camera trapping efficiency in studying daily activity patterns of Turkestan lynx in the Northern Tien Shan (Eurasian Journal of Ecology, 2023)
In order to determine the relationship between elusive carnivorans and other species, understand the mechanisms of their adaptation in the environment, as well as for regulation of strategies for rare carnivores’ conservation, it is relevant and necessary to study their daily activity rhythms. As a nocturnal species in the remote mountains of the Northern Tien Shan, the behavioral ecology and, in particular, the activity rhythms of the Turkestan lynx (Lynx lynx isabellina Blyth, 1847) are poorly studied. This article presents data on the daily activity of the lynx and an analysis of its correlation with the activity rhythms of its prey species in the Northern Tien Shan using camera traps. As a result of research conducted in Ile and Kungei Alatau from 2013 to 2022, we used 11,258 trap-days and obtained 59 frames with individual passages of Turkestan lynx and 528 frames with passages of its prey species – tolai hare (Lepus tolai), Siberian roe deer (Capreolus pygargus), Siberian ibex (Capra sibirica), wild boar (Sus scrofa), red tree squirrel (Sciurus vulgaris exalbidus) and red deer (Cervus elaphus). The rhythms of lynx’s daily activity coincided with the activity of its prey in three different time peaks: in the early morning, in the afternoon, and at night. Tolai hare in Kungei Alatau and Siberian roe deer in Ile Alatau play a significant role in the conservation of the lynx population. The results obtained prove the need to protect these six species to ensure the Turkestan lynx populations stability in the Northern Tien Shan.Keywords: Turkestan lynx, daily activity, specially protected natural areas, camera traps